Elasticity of Demand to Increase in Gold Prices from an Islamic Economic Perspective - Nas’al Salsabela; Elis Ratna Wulan (CV. Civiliza Publishing, 2026)
The phenomenon of rising global gold prices that does not proportionally reduce the volume of demand among the Indonesian Muslim community, possibly the demand is inelastic, with the aim of analyzing the level of elasticity and interpreting it from an Islamic economic perspective. The method used is a literature study by analyzing secondary data on prices and sales of gold bullion from PT Antam Tbk, which is analyzed using the calculation of the price elasticity coefficient of demand (E_d = %ΔQ / %ΔP) and interpreted through the principles of Islamic economics. The results show that a drastic annual gold price surge of 65.08% was only followed by a minor contraction in domestic demand volume of 14.64%, resulting in an E_d value of -0.22502 which confirms the inelastic nature of gold demand. This study reveals that this inelastic nature is consistent with the characteristics of gold as a safe-haven asset whose demand is more influenced by macroeconomic factors, and from an Islamic perspective this finding aligns with maqasid al-shari'ah, specifically hifz al-mal (preservation of wealth), where gold functions justly (‘adl) and balancedly (tawazun) in maintaining public purchasing power while still fulfilling the principle of mutual consent (an-taradin) in transactions. This study recommends further research using multiple regression or data panel econometrics analysis by integrating other external macroeconomic variables